Gender Gaps in Financial Literacy: A Multi-Arm RCT to Break the Response Bias in Surveys - Laura Hospido; Nagore Iriberri; Margarita Machelett (Institute of Labor Economics (IZA), 2023)
Gender gaps in financial literacy are pervasive and persistent. They are partly explained because women choose "I do not know" more frequently. We test for the effectiveness of three interventions to shift this behavior. The control survey includes the possibility of "I do not know". The three treatments either exclude this possibility, offer incentives for correct answers, or inform survey takers of the existing gender gap in choosing this answer option. While all interventions are very effective in reducing this answer option, only the information significantly reduces the gender gap in "I do not know" and in financial literacy.
Keywords: C8; C9; D14; D91; G53; I22; J16; 330; financial literacy; gender gaps; survey methods